Recovery of Various Metals from Industrial Wastewater by Biological Methods - Ojha A.; Mishra A.; Tiwary D.; Singh A. (My University, 2025)
Industrial wastewater contains a variety of hazardous chemicals as well as high metal concentrations. Metal-contaminated wastewater is hazardous to the environment and can have serious health consequences if it enters biological systems. However, the recovery of metals from wastewater can increase the sustainability of treatment processes and enhance cost-effectiveness. There are numerous conventional treatment methods for recovering metals from wastewater, including physical, chemical, and even biological methods. Physical and chemical processes are primarily energy and chemical-intensive. New-age research uses novel bio-recovery methods to extract and remove metals from wastewater. Various methods like sorption, biomembranes, bioelectrochemical techniques, etc., have been discussed in this chapter in a summarized form. Further, insights into energy-efficient recovery methods and their applications have been elaborated. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.